Demand Analysis of Sweet Orange Fruit in Kendari City - Nanda Iman Hidayat; R. Marsuki Iswandi; Munirwan Zani (International journal of technology and education research, 2024)
This research aims to determine 1) The demand for sweet oranges in Kendari City and 2) the factors that influence the demand for sweet oranges in Kendari City. The research was deliberately determined from June to August 2023 in the traditional market of Kendari City. The sampling technique in this research was determined by incidental sampling. Incidental sampling is a technique for determining samples based on chance, that is, anyone who coincidentally/incidentally meets the researcher can be used as a sample if it is deemed that the person they happen to meet is suitable as a data source. Technique The sample in this study was 40 oranges sweet consumers. This data analysis uses multiple linear regression analysis using the SPSS application. The variables observed in this research are the price of sweet oranges, the price of mangoes, income, age and number of family members. The results of the research are that the average demand for sweet oranges in Kendari City is 2.6 kg/week and the factors that significantly influence the demand for sweet oranges in Kendari City are the price of sweet oranges, the price of mangoes, income and the number of family members (α < 0.05). Age has no significant effect on demand for sweet oranges in Kendari City (α > 0.05).